2020
DOI: 10.1103/physrevlett.124.106104
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Dislocations in 3.9 nm Nanocrystals at High Pressure

Abstract: As circuitry approaches single nanometer length scales, it is important to predict the stability of metals at these scales. The behavior of metals at larger scales can be predicted based on the behavior of dislocations, but it is unclear if dislocations can form and be sustained at single nanometer dimensions. Here, we report the formation of dislocations within individual 3.9 nm Au nanocrystals under nonhydrostatic pressure in a diamond anvil cell. We used a combination of x-2 ray diffraction, optical absorba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…4,5 Because properties depend on nanoparticle shape and size, the performance in these applications depends on the stability of the particle, and its resistance to any mechanical loading or shearing during use. Therefore, understanding the mechanical properties of metal nanoparticles is vital for controlling their performance.Great strides have been made in the experimental measurement of the mechanical properties of metal nanoparticles, including with diamond anvil cells, 6,7 and with in situ compression inside a scanning electron microscope (SEM) 8,9 or a transmission electron microscope (TEM). [10][11][12] These techniques have been extensively applied to larger nanoparticles, with diameters in the range of tens to hundreds of nanometers, but are more challenging to apply to smaller nanoparticles with diameters in the range of 10 nm and below, so the understanding of nanoparticle deformation in this size regime remains incomplete.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Because properties depend on nanoparticle shape and size, the performance in these applications depends on the stability of the particle, and its resistance to any mechanical loading or shearing during use. Therefore, understanding the mechanical properties of metal nanoparticles is vital for controlling their performance.Great strides have been made in the experimental measurement of the mechanical properties of metal nanoparticles, including with diamond anvil cells, 6,7 and with in situ compression inside a scanning electron microscope (SEM) 8,9 or a transmission electron microscope (TEM). [10][11][12] These techniques have been extensively applied to larger nanoparticles, with diameters in the range of tens to hundreds of nanometers, but are more challenging to apply to smaller nanoparticles with diameters in the range of 10 nm and below, so the understanding of nanoparticle deformation in this size regime remains incomplete.…”
mentioning
confidence: 99%
“…Great strides have been made in the experimental measurement of the mechanical properties of metal nanoparticles, including with diamond anvil cells, 6,7 and with in situ compression inside a scanning electron microscope (SEM) 8,9 or a transmission electron microscope (TEM). [10][11][12] These techniques have been extensively applied to larger nanoparticles, with diameters in the range of tens to hundreds of nanometers, but are more challenging to apply to smaller nanoparticles with diameters in the range of 10 nm and below, so the understanding of nanoparticle deformation in this size regime remains incomplete.…”
mentioning
confidence: 99%
“…The development of the computational tools accounting for the dislocational nature of plastic flows has become a priority because the inadequacy of the conventional methods based on CP was placing severe restrictions on the possibility to model plastically deforming ultra-small structural elements [22,[88][89][90]. In particular, it was realized that to simulate discontinuous yielding in sub-micron crystals which involves massive nucleation of dislocations, the modeling approach cannot ignore lattice effects and must necessarily account for phenomena at the scale of dislocation cores.…”
Section: Some Backgroundmentioning
confidence: 99%
“…MD approaches, including Molecular Statics (MS), and Density Functional Theory (DFT), accurately represent micro-mechanisms of plastic response while relying minimally on phenomenology [112]. MD simulations have been particularly instrumental in the study of the homogeneous and heterogeneous dislocation nucleation [76,90,97]. The only relative shortcoming of the atomistic simulations is that they are still computationally rather expensive in most applications, even at the small time and length scales of interest; also the problem of mapping to the macroscopic description in terms of the measurable quantities like stresses and strains is apparently not yet fully resolved [113][114][115][116].…”
Section: Some Backgroundmentioning
confidence: 99%
“…For example, the dependence of strength and deformation on particle size and shape has been investigated. Studies on the deformation of faceted gold nanoparticles using an anvil cell [73] have shown the occurrence of Shockley dislocations along facet vertices. However, to prevent sintering, the maximum load achieved with this method is limited, and the stress cannot be calculated directly, instead it is inferred from lattice changes.…”
Section: Introductionmentioning
confidence: 99%